Investigating the influence of environmental factors on the incidence of renal disease with compositional data analysis using balances. (June 2020) - McKinley, Jennifer M.; Mueller, Ute; Atkinson, Peter M.; Ofterdinger, Ulrich; Jackson, Chloe; Cox, Siobhan F.; Doherty, Rory; Fogarty, Damian; Egozcue, J.J.; Pawlowsky-Glahn, V.
Abstract: This research uses an urban soil geochemistry database of elemental concentration to examine the potential relationship between Standardised Incidence Rates (SIRs) of Chronic Kidney Disease (CKD) of uncertain aetiology (CKDu), and cumulative low level geogenic and diffuse anthropogenic contamination of soils with PTEs. A compositional data analysis approach was applied to determine the elemental balance(s) of the geochemical data showing the greatest association with CKDu. The research concludes that both anthropogenic and geogenic factors may be contributing influences to explain high incidences of CKDu, up to 12 times greater in some Super Output Areas (SOAs) than would be expected for the average population. The role of As, Cr, Cu, Pb, Sb and Mo was highlighted, which may be linked to anthropogenic sources such as historical industrial sources, atmospheric pollution deposition and brake emissions. Geogenic factors were shown to be important in areas with elevated relative concentrations of naturally occurring potentially toxic elements (PTEs).